ANALISIS PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP MINAT PEMBELIAN PRODUK TABUNGAN DI BANK BNI SYARIAH DEPOK DENGAN CITRA PERUSAHAAN SEBAGAI VARIABEL MODERASI - Handayani, Tati; S, Ratih Mulya W. (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2014)
Corporate Social Responsibility lately has become the main topic arround the business companies in Indonesia. In order to grow the business, they use corporate social responsibility to get the public symphaty. Even the sharia bank of BNI use the social activities and publicity to increase the purchase intention of their savings product. There is a relation between CSR and corporate image and then affect the purchase intention, and this is one of the purpose of this research. This research take 100 samples from BNI Sharia customers who knows about the CSR and who already had the savings product. This study was held at BNI Sharia in Depok to identify the purchase intention of savings product among the citizen. The results of this research are CSR positively and significantly affecting purchase intention and corporate image also positively and significantly affecting purchase intention. another results of this research is There is an interaction between CSR and corporate image and corporate image positively and significantly has function as a moderate variable that influence CSR to purchase intention.